2013
DOI: 10.3109/02770903.2013.853080
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of living with asthma – a focus group study with adolescents and parents of children with asthma

Abstract: Living with asthma leads to developing personal strategies in self-management of asthma. Moreover both parents and adolescents had expectations of being met by competent and understanding health care professionals. Developing a partnership between patients and health care professionals could be a successful way to improve the care of patients with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
64
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 156 publications
(177 reference statements)
3
64
2
3
Order By: Relevance
“…These findings are not surprising given that previous studies have shown that adolescents want to avoid appearing different from their peers, which can lead to denying, hiding, or ignoring symptoms and subsequent failure to use medication in the presence of others. [29] This may also explain why only three of twenty adolescents recruited friends to participate in the study. Adolescents may have been uncomfortable asking their friends to participate in an activity that focused on their asthma; thereby, emphasizing how they were different from their friends.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are not surprising given that previous studies have shown that adolescents want to avoid appearing different from their peers, which can lead to denying, hiding, or ignoring symptoms and subsequent failure to use medication in the presence of others. [29] This may also explain why only three of twenty adolescents recruited friends to participate in the study. Adolescents may have been uncomfortable asking their friends to participate in an activity that focused on their asthma; thereby, emphasizing how they were different from their friends.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents with asthma are a specific group of patients with different problems and needs comparison with children and adults with asthma. The disease varies a lot during growth, which needs to be taken into account when treating an adolescent with asthma . Developmental behavior, peer pressure, and the difficult transition to health care leads to under‐diagnosis and under‐treatment of asthma in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Most evidence relating to the experience of growing up with a long‐term condition and the impact this may have on a child's expected developmental trajectory (Venning, Eliott, Wilson, & Kettler, ) is quantitative and addresses the perspectives of older children and adolescents (e.g., Smith, Taylor, Newbould, & Keady, ) with diabetes, asthma, cystic fibrosis, and rheumatic conditions (see, e.g., Cartwright, Fraser, Edmunds, Wilkinson, & Jacobs, ; Jessup & Parkinson, ; Jonsson, Egmar, Hallner, & Kull, ; Marshall, Carter, Rose, & Brotherton, ). The impact and influence of a long‐term condition on adolescents tend to be reported in terms of the young people's resilience and how the young people adjust to and aim for control over the disruption associated with the condition (Cartwright et al., ; Ferguson & Walker, ; Tong, Jones, Craig, & Singh‐Grewal, ).…”
mentioning
confidence: 99%